Socio-economic aspects of reclaimed bauxite lands in Jamaica : farming issues, problems and possible solutions - Lyew-Ayee, Parris A. (1999)
Discusses the results of a socio-economic survey of farmers who presently make use of reclaimed lands for farming in the parishes of Manchester and St. Ann. Highlights major issues from the farmer's viewpoint. which impact significantly on the success of a farm and revisits common prblems. Discusses workable, cost-effective company/government approaches towards possible solutions, with a view to triggering greater emphasis on zoned farm lands as an integral part of community development.